Leishmanicidal activity of methanolic extract from four ecotypes of Lepidium peruvianum, Chacón (Brassicaceae) - Alzamora, Libertad (2006)
The classic treatment of the cutaneous leishmaniosis consists on the injection of 15-20 ampoule of Glucantine what causes serious secondary effects. This fact justifies the search of new medications what motivated the present investigation. The objective was to evaluate the leishmanicidal activity of the methanolic extracts (ME) of the white, red, purple and black ecotypes of Lepidium peruvianum Chacón (at present Lepidium meyenii Walp.) about the growth of Leishmania braziliensis peruviana in vitro. The promastigotes reached the logarithmic phase to the fifth day of cultivation at 27 ºC in the two-phase Columbia medium with 15% of defibrinated sheep blood and they faced, for separate, with the ME to concentrations of 50, 100, 200 and 400 μg/ml. The recounts were made daily with camera Neubauer. The maximum decrease of promastigotes (17.41% of viability) took place to the second day for the purple ecotype with the concentration of 400 μg/ml. The leishmanicidal effect would be related with the imidazolic alkaloids, glucosinolates, flavonoids, tannins and saponines present in the ME. The conclusion is that only ME of the white and purple ecotypes presents leishmanicidal activity, at second day of culture.